1997
DOI: 10.1113/expphysiol.1997.sp004063
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the maternal and fetal renin‐angiotensin systems in response to angiotensin II type 1 receptor blockade and angiotensin‐converting enzyme inhibition in pregnant sheep during late gestation

Abstract: SUMMARYThe effects of maternal administration of either an angiotensin II type 1 (AT1) receptor antagonist (GR 138950) or an angiotensin-converting enzyme (ACE) inhibitor (captopril) on the renin-angiotensin system (RAS) were investigated in chronically catheterized ewes and their fetuses during late gestation. From 127 + 1 days of gestation until parturition at 145 + 2 days, each ewe received daily I.v. injections of GR138950 (3 mg kg-1, n = 10 animals) or captopril (3 mg kg-1, n = 6) or an equivalent volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To minimize potential confounding effects of renin-angiotensinogen molecules in serum [32], we employed a granulosa cell culture system in which treatments were applied under defined conditions. Bovine ovaries were collected from adult cows, irrespective of stage of the estrous cycle, at a local abattoir and were transported to the laboratory in PBS at 358C containing penicillin (100 IU/ml), streptomycin (100 lg/ml), and fungizone (1 lg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…To minimize potential confounding effects of renin-angiotensinogen molecules in serum [32], we employed a granulosa cell culture system in which treatments were applied under defined conditions. Bovine ovaries were collected from adult cows, irrespective of stage of the estrous cycle, at a local abattoir and were transported to the laboratory in PBS at 358C containing penicillin (100 IU/ml), streptomycin (100 lg/ml), and fungizone (1 lg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…In the GR-treated fetuses, the activity of the AT 2 receptor in the kidney is likely to increase not only by upregulation of receptor protein content but also by binding of elevated circulating levels of AII. Plasma AII concentration is raised during AT 1 receptor antagonism due to a decrease in feedback inhibition of renin production by AII via AT 1 receptors (Forhead et al 1997, de Gasparo et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extent to which AT 1 receptor blockade influences renal expression of the AT 1 and AT 2 receptor subtypes is unknown in the developing kidney. Changes in AT 2 receptor expression are of particular interest as the unblocked receptor subtype is exposed to high concentrations of AII following loss of negative feedback on renin release during AT 1 -specific receptor antagonism (Forhead et al 1997, de Gasparo et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…125 More recently it has been found that the RAAS system is more active in the placental vascular beds of preeclamptics compared to normal patients. 127 Angiotensin II from the mother is probably required for trophoblast invasion of the endometrium in mammals. 126 There is a very active RAAS system in the fetus and this becomes more active with Angiotensin converting enzyme (ACE) blockade.…”
Section: Renin Angiotensin System (Raas)mentioning
confidence: 99%